Play and Learn: Introduction of Robotics to the Library - Molnár, Dániel; Dani, Erzsébet (Central European Journal of Educational Research, 2022)
Our library, the Katona József Library of Bács-Kiskun County, has recently started to introduce the basics of robotics, currently with LEGO Mindstorm kits. LEGO robots are programmed using a simple, graphical interface, making it easy for anyone to learn. Our main objective is to show the public that robotics is not just a thing of the future, but an important element of our time today. We see our work in this direction as a “first step”. Considering different possibilities and needs, two types of programmes on robotics have been developed. The shorter, one-hour session will present the way to robotics in the modern sense, through examples of cultural and technological history and current applications. This will be followed by a playful trial of three different robots on display. For those who want to learn more about robots, we offer a weekly “Library Robot Hour”, a club-like service where you can learn how to code robots and solve specific tasks, either with help or independently at your own pace.